Efecto de la temperatura de recocido sobre la resistencia al impacto y dureza de una fundición nodular astm a536 en la obtención de una fundición nodular ferrítica - Fabián Guzmán, Tony Alexander (2018)
In the present investigation, the effect of the annealing temperature in a nodular cast iron ASTM A536 on the hardness, impact resistance and microstructure in obtaining a ferritic nodular cast iron was studied. For this purpose we used square bars of 15 mm x 15 mm x 200 mm in length supplied by Fundición Laminar SAC - Lima, where the specimens were machined for the hardness test according to the ASTM E- 140 standard and for the impact test according to ASTM E23-98, which were annealed at temperatures of 800, 850, 900, 950 and 1000 ° C for a time of 25 hours with slow cooling inside the oven. The results show that when the annealing temperature is increased, the hardness decreases from 198.40 HB for supply (25°C) to 114.80 HB for 1000°C annealing temperature, and the impact resistance (J) increases as the temperature increases. annealed from 53.90 J for supply (25°C) up to 124.20 J for 1000°C. This is due to the decomposition of austenite in ferrite that increases as the annealing temperature increases, being the total or total transformation of austenite in ferrite under the study conditions from 900°C, from which a ferritic nodular cast iron and that the graphite nodules (Gn) are stable at any annealing temperature under study. It is concluded that the annealing temperature significantly affects the hardness, impact resistance and microstructure, and that the minimum temperature for obtaining a ferritic nodular cast iron in the study conditions is 900°C. The results obtained have been contrasted with a statistical analysis with a confidence level of 95%.